54‐2: Fabrication of Ink‐jet printing Quantum‐Dots Light Emitting Diodes using Optimization of Co‐solvent Condition. Issue 1 (29th May 2019) - Han, Young-Joon; Kang, Kyung-Tae; Ju, Byeong-Kwon; Cho, Kwan-Hyun
Abstract : In this research, we introduce the fabrication of ink‐jet printed quantum‐dot light emitting diodes (QLEDs) using optimization of co‐solvent condition. Generally, in the fabrication of QLEDs, pinholes and dewetting on the surface of quantum‐dot (QD) thin films in the pixel cause performance degradation of the QLEDs. To control this problem, we dispersed QDs with CdZnSeS structure at a concentration of 20 mg/ml in a 1: 2 mixture of hexane and dichlorobenzene (oDCB). In addition, for stabilization of the jetting process, cartridge meniscus and waveforms were optimized. As a result, a uniform QD thin film was formed on a 240μm × 60μm bank pixel array. No pinholes or drying phenomena were found on the ink‐jet printed QD thin film surface. The luminance, current efficiency, and quantum efficiency of the fabricated ink‐jet printing QLEDs were 6319.6 cd/m 2, 4.21 cd/A, and 1.03 %, respectively. The fabricated ink‐jet printing QLEDs showed a luminance of 13.33%, a current efficiency of 23.8%, and a quantum efficiency of 23.62% as compared with those of the spin‐coated QLEDs.